PAVEL HIML, JAN SEIDL, FRANZ SCHINDLER, (edd.), „Miluji tvory svého pohlaví“. Homosexualita v dějinách a společnosti českých zemí, Praha 2013, Argo, 650 s., ISBN 978-80-257-0876-7 - Mareš, Jan (Dějiny – teorie – kritika, 2014)
Book review